2017
DOI: 10.1016/j.healthplace.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

How ‘social’ is recreational running? Findings from a qualitative study in London and implications for public health promotion

Abstract: Recreational running is increasingly widespread and could therefore be seen as the obvious target for those hoping to encourage greater public health through exercise. Existing qualitative research on this topic has, however, tended to focus on groups of highly committed runners. It is accordingly unclear whether their findings can be extrapolated to the much larger population of comparatively casual runners. This existing work has also tended to emphasise the social nature of the activity in particular ways. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 38 publications
0
45
0
1
Order By: Relevance
“…DeLand (2012), Crossley (2004), Wilste (2007), Tonkiss (2013), Hitchings and Latham (2017a), Jackson (2019).…”
Section: The Spaces and Socialities Of Social Infrastructurementioning
confidence: 99%
“…DeLand (2012), Crossley (2004), Wilste (2007), Tonkiss (2013), Hitchings and Latham (2017a), Jackson (2019).…”
Section: The Spaces and Socialities Of Social Infrastructurementioning
confidence: 99%
“…Overall, the experience of the social and that of the physical environment appears strongly interlinked for the participants of running events, while different 'kinds' of runners seem to appreciate different aspects of sociality (see Hitchings and Latham 2017a). Similarly-and this has remained underexposed in the literature that tends to be biased in its focus on committed runners (ibid.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the studies in question regard running events as signs of commodification and urban boosterism (Nettleton and Hardey 2006;Herrick 2015) that fit broader processes of 'festivalisation' (Richards 2007) and 'eventification', strategically devised by urban governments to stage and market the 'city product' (Jakob 2013). However, a larger share of the ever-expanding literature on running (events) has taken a more bottom-up perspective and has variously highlighted aspects of sociability (Sheehan 2006;Shipway et al 2012;Robinson et al 2014;Hitchings and Latham 2017a), mobility (Cidell 2014), and-in some cases relying on autoethnographic insights (e.g. Allen-Collinson 2003;Hockey 2006;Lorimer 2012;Barnfield 2017)-has discussed running in terms of (individual and collective) embodied experiences (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on theories by Bourdieu (2013), as well as studies on runners (Nettleton 2013;Tulle 2007), arguments have been put forth that the social capital of being a runner is an important driving factor behind the choice to run and participate in races. Whilst new research has suggested that these aspects are less important than previously thought, at least with regards to casual runners (Hitchings and Latham 2017), in similarity to making other health-related choices, running can signal that an individual has acknowledged an understanding of the risks of inactivity, the benefits running can confer, has accepted recommendations of health experts, and is taking responsibility for managing his or her own risk (Shipway and Holloway 2010). Also, attaining the distance running body has been argued could be considerable 'cultural capital' given the Western society's bodily ideals of representing healthiness (Bridel, Markula, and Denison 2015).…”
Section: Introductionmentioning
confidence: 95%